Antioxidant Activity and Acteoside Analysis of Abeliophyllum distichum - Hak-Dong Lee; Ji Hyun Kim; Qi Qi Pang; Pil-Mun Jung; Eun Ju Cho; Sanghyun Lee (Antioxidants, 2020)
This study determined acteoside and its content in Abeliophyllum distichum via HPLC/UV and LC/ESI-MS to obtain insights into the potential use of this plant as an antioxidant agent. Moreover, 1,1-diphenyl-2-picrylhydrazyl (DPPH), hydroxyl (•OH), and O2− radical scavenging activity assays were performed to assess in vitro antioxidative activity. The DPPH, •OH, and O2− radical scavenging activities of A. distichum leaf EtOH extracts at a 250 μg/mL concentration were 88.32%, 94.48%, and 14.36%, respectively, whereas those of stem extracts at the same concentration were 88.15%, 88.99%, and 15.36%, respectively. The contents of acteoside in A. distichum leaves and stems were 162.11 and 29.68 mg/g, respectively. Acteoside was identified as the main antioxidant compound in A. distichum leaves, which resulted in DPPH, •OH, and O2− radical scavenging activities of 82.84%, 89.46%, and 30.31%, respectively, at a 25 μg/mL concentration. These results indicate that A. distichum leaves and stems containing the antioxidant acteoside can be used as natural ingredients for functional and nutritional supplements.